Remote monitoring of structural health in composites. Issue 1 (January 2017) - Golchinfar, Behnoush; Donskoy, Dimitri; Pavlov, Julius; Rutner, Marcus
Abstract: Dedicated to Prof. Dr. Eng. Akimitsu Kurita on his 70th birthday, in honour of his scientific achievements, guidance and the education of his students. This paper explores a new interdisciplinary method for internal damage detection and tracking in composite materials using thermo‐chemical sensing. A micro‐sized network of strings is interwoven into the composites. Each string consists of a pair of tubes containing one of two different non‐polar reactants. A local defect within the composites causes straining and cracking of the tube shell, resulting in direct contact between the two non‐polar reactants. The latter undergo a chemical reaction resulting in a polar product. When exposed to a microwave energy source, a polar product heats up dramatically within seconds in comparison to the surrounding composite material or the non‐polar reactants. This localized thermal signature can be rendered visible by an infrared camera. This study summarizes the findings of an in‐depth computational and experimental study of this sensing technology which is expected to be applicable across industries using composites, among them aerospace, automotive, offshore and bridge engineering. Potential applications in steel offshore or steel bridge engineering involve using composite sensing patches to cover fatigue fracture‐critical components. Defects initiating on the steel substrate surface are expected to be sensed on demand with this proposed sensing technology.